Trabalho, educação profissional e reestruturação produtiva : um estudo do ensino técnico integrado ao ensino médio no Campus Anápolis do IFG - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This work, a qualitative approach, aims to analyze the training provided to students of the integrated technical courses at the Federal Institute of Education, Science and Goiás Technology (IFG), taking as empirical object the campus Annapolis, from the study of the relationship between work and education in capitalist society, especially of the changes arising from the restructuring process of the 1970s Besides bibliographical study, with theoretical support Antunes (2005, 2011), Cunha (2000), Frigotto (1999, 2010, 2012), Kuenzer (1991, 2009, 2011, 2012), Ramos (2012), among others, the research involved document analysis and empirical research through questionnaires with the coordinators and senior students of technical courses integrated into the high school of the Annapolis campus IFG, plus an interview with the general director of that campus. The analyzes allow us to infer that the constitution of the Federal Institutes of Education, Science and Technology permeates the history of education in Brazil, becoming in every historical moment, according to the economic, political, social and cultural scene experienced in the country. The very meaning of work has been transformed over time, away from its essence as production of human existence, is degrading as a result of capitalist exploitation. The proposed integrated technical education to high school, which we believe is a right of the working class, would, in theory, ensure the student training, often necessary for survival and even the continuation of studies and solid general education, omnilateral thus ensuring formation of subjects in a training perspective integrated. The research points out some positive aspects in the training of students of integrated technical courses, especially in the field of general education. However, some challenges still need to be overcome, including the construction itself of the identity of integrated technical courses, difficulties in curriculum integration and in the organization of courses, especially with regard to excess disciplines and limitations in the field of vocational training.
Keywords: Trabalho; Educação profissional; Ensino Técnico Integrado; Work; Professional education; Integradet Technical Education; CIENCIAS HUMANAS::EDUCACAO